Triglycidyl para-aminophenol modified montmorillonites for epoxy nanocomposites and multi-scale carbon fiber reinforced composites with superior mechanical properties. (18th August 2017) - Peng, Mao; Zhou, Yang; Zhou, Guodoong; Yao, Huichao
Abstract: Multi-scale carbon fiber reinforced polymer (CFRP) composites with continuous carbon fiber as the primary reinforcement and nanoscale fillers as the secondary reinforcement have attracted great research interests in the last decade. Herein we report a new organically modified montmorillonite (MMT) for epoxy nanocomposites and multi-scale CFRP composites with superior mechanical properties. The organically modified MMT is prepared by ion-exchanging natural MMT with the hydrochlorate of triglycidyl para -aminophenol (TGPAP), a tertiary amine-type epoxy oligomer used as a CFRP matrix for the aerospace industry. The TGPAP-modified MMTs disperse uniformly in the matrix as thin stacks of intercalated nanoplatelets and exfoliated single-layer nanoplatelets, and are reactive with the epoxy matrices, thus remarkably enhance the mechanical properties of the nanocomposites and multi-scale CFRP composites. In contrast to reference CFRP composites, the incorporation TGPAP-modified MMTs greatly retards the propagation of inter-layer delamination, and fiber breakage becomes the major damage mode in the three-point bending tests. In particular, 4 wt% of TGPAP-modified MMTs increases the interlaminar shear strength of the multi-scale CFRP composites by 52%, and the flexural strength by 52.3%, which is superior to those of MMT-containing CFRP composites ever reported.